Adipose tissue immunity and cancer - Catalan, Victoria; Gomez-Ambrosi, Javier; Rodríguez, Amaia; Frühbeck, Gema (Frontiers in Physiology, 2013)
Inflammation and altered immune response are important components of obesity and contribute greatly to the promotion of obesity-related metabolic complications, especially cancer development. Adipose tissue expansion is associated with increased infiltration of various types of immune cells from both the innate and adaptive immune systems. Thus, adipocytes and infiltrating immune cells secrete proinflammatory adipokines and cytokines providing a microenvironment favourable for tumour growth. Accumulation of B and T cells in adipose tissue precedes macrophage infiltration causing a chronic low-grade inflammation. Phenotypic switching towards M1 macrophages and Th1 T cells constitutes an important mechanism described in the obese state correlating with increased tumour growth risk. Other possible synergic mechanisms causing a dysfunctional adipose tissue include fatty acid-induced inflammation, oxidative stress, endoplasmic reticulum stress, and hypoxia. Recent investigations have started to unravel the intricacy of the cross-talk between tumour cell/immune cell/adipocyte. In this sense, future therapies should take into account the combination of anti-inflammatory approaches that target the tumour microenvironment with more sophisticated and selective anti-tumoural drugs.